1997
DOI: 10.1111/j.1540-8167.1997.tb00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine‐Sensitive Atrial Reentrant Tachycardia Originating from the Atrioventricular Nodal Transitional Area

Abstract: There may be an entity of adenosine-sensitive atrial tachycardia probably due to focal reentry within the AV node or its transitional tissues without involvement of the AV nodal pathways. This tachycardia can be ablated without disturbing AV nodal conduction from the right atrial septum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
154
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(160 citation statements)
references
References 27 publications
4
154
1
1
Order By: Relevance
“…Since this form of AT was sensitive to adenosine and verapamil, a calcium channel–dependent tissue has been suggested to be involved in the reentry circuit 4, 5, 6, 7, 8, 9. Indeed, cells with atrioventricular nodal or transitional‐type action potentials have been shown to be present in the atrioventricular valve 16, 17, 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this form of AT was sensitive to adenosine and verapamil, a calcium channel–dependent tissue has been suggested to be involved in the reentry circuit 4, 5, 6, 7, 8, 9. Indeed, cells with atrioventricular nodal or transitional‐type action potentials have been shown to be present in the atrioventricular valve 16, 17, 18.…”
Section: Discussionmentioning
confidence: 99%
“…These SPs, which were observed in the region along the septal tricuspid annulus close to the coronary sinus (CS) ostium, can be a marker for successful slow pathway ablation, suggesting that the SP reflects a substrate of slow pathway composed of calcium channel–dependent tissue. Meanwhile, it has also been shown that calcium channel–dependent tissue is involved in the tachycardia circuit of verapamil‐sensitive atrial tachycardia (AT) arising from the atrioventricular annulus 4, 5. We have recently shown that the underlying mechanism of the verapamil‐sensitive AT arising from the atrioventricular annulus is caused by reentry with a slow conduction zone (SCZ) involved in the circuit 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] More recently, Ino et al described a case with a 2:1 exit block of repetitive focal activity in a SVC focus manifesting as a high right AT. 13 Furthermore, we found that AT can occur focally from different parts of the SVC, which was confirmed by the SVC angiogram showing the location of the successful ablation sites at various distances above the atriocaval junction and different positions within the SVC (Fig 7).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Focal AT is distinguished from macroreentrant AT by its electrophysiological characteristics and electropharmacological responses, and by the approaches to mapping and ablation of the tachycardia. 7,8 The underlying mechanism of focal AT is thought to be automaticity, triggered activity or atrial microreentry.…”
mentioning
confidence: 99%
“…13,14 These ATs resemble the fast/slow form of AV node reentry with respect to ECG characteristics and electrophysiological properties. Earliest atrial activation is recorded from the low anteroseptal RA, and these tachycardias are sensitive to adenosine and verapamil.…”
Section: Focal Atrial Tachycardia: "Ring Of Fire"mentioning
confidence: 99%